A Triple Fixed Point Theorem for Multimap in a Hausdorff Fuzzy Metric Space - K. P. R. Rao; K. R. K. Rao (Journal of Mathematics)
We obtain two triple fixed point theorems for a multimap in a Hausdorff fuzzy metric space.